Effect of mitomycin C-aided trabeculectomy on conjunctival goblet cell density - Mukhopadhyay, S; Thakur, SKD; Dutta, J; Prakash, R; Shaw, C; Gangopadhyay, DN; Dutta, H; Bhaduri, G (Nepalese Journal of Ophthalmology, 2012)
Introduction: Mitomycin C is gaining widespread popularity as an adjunctive with trabeculectomy, as it significantly increases the success rate of the procedure. But it is associated with serious sight-threatening complications. Materials and methods: Twenty eyes planned for trabeculectomy from the glaucoma clinic were enrolled for the study after obtaining an informed consent. The baseline impression cytology was taken. Ten eyes underwent trabeculectomy with mitomycin C (Group A) and the rest underwent trabeculectomy without any antimetabolites (Group B). Impression cytology samples were taken on months 1, 3, 6, 9 and 12. Results: In Group A, the difference between goblet cell density preoperatively and 12 month postoperatively was statistically significant (p < 0.0001). In Group B, the difference was not statistically significant. (p = 0.27). Conclusion: Mitomycin C, though used to augment the success rate of trabeculectomy, has deleterious effect on the conjunctival goblet cell population as is evident from the conjunctival impression cytology. DOI: http://dx.doi.org/10.3126/nepjoph.v4i1.5854 NEPJOPH 2012; 4(1): 68-72